Daily life participation in childhood chronic disease: a qualitative study on the child's and parent's perspective - Marijke C Kars; Martha A Grootenhuis; Cornelis K van der Ent; Joost F Swart; Elise M van de Putte; Sanne L Nijhof; Emma E Berkelbach van der Sprenkel; Linde N Nijhof; Annet van Royen-Kerkhof (BMJ Publishing Group, 2021)
Objective To understand how a child with a stable chronic disease and his/her parents shape his/her daily life participation, we assessed: (1) the parents' goals regarding the child's daily life participation, (2) parental strategies regarding the child's participation and () how children and their parents interrelate when their goals regarding participation are not aligned.Methods This was a qualitative study design using a general inductive approach. Families of children 8-19 years with a stable chronic disease (cystic fibrosis, autoimmune disease or postcancer treatment) were recruited from the PROactive study. Simultaneous in-depth interviews were conducted separately with the child and parent(s). Analyses included constant comparison, coding and categorisation.Results Thirty-one of the 57 invited families (54%) participated. We found that parents predominantly focus on securing their child's well-being, using participation as a means to achieve well-being. Moreover, parents used different strategies to either support participation consistent with the child's healthy peers or support participation with a focus on physical well-being. The degree of friction between parents and their child was based on the level of agreement on who takes the lead regarding the child's participation.Conclusions Interestingly, parents described participation as primarily a means to achieve the child's well-being, whereas children described participation as more of a goal in itself. Understanding the child's and parent's perspective can help children, parents and healthcare professionals start a dialogue on participation and establish mutual goals. This may help parents and children find ways to interrelate while allowing the child to develop his/her autonomy.